A 30-Year Retrospective: Degrees of Difficulty in Decreasing LOS. Issue 5 (September 2016) - Zander, Karen
Abstract : Purpose: In an attempt to avoid future revisionist history, the author offers a 30-year retrospective (1986–2016) on the evolution of strategies to reduce length of stay (LOS). She and her colleagues have been involved from the onset by developing tools such as critical paths, roles such as clinical case management, and operational systems for managing measureable outcome-driven care from the bedside to the boardroom. Primary Practice Setting: Acute care hospitals. Findings/Conclusions: The LOS for all inpatients has changed dramatically from 1970 (average LOS = 7.8 days) through solidly between 2005 and 2012 (average LOS = 4.5 days in 2012) despite a significant increase in the average age of hospital inpatients (C. J. DeFrances & M. J. Hall, 2007 ;A. Weiss & A. Elixhauser, 2014 ). For patients 65 years and older, who comprised 38% of all inpatients, the decrease has been more drastic: from 12.6 days in 1970 to 5.5 days in 2005–2010 (CDC/National Center for Health Statistics, 2010 ). With the exception of hospitalists and case management staff, acute care hospitals have essentially doubled productivity without adding additional direct care full-time equivalents! Described in terms of "low-hanging" to "high-hanging" fruit, this article outlines the classic methods used to reduce LOS and concludes with some implications of LOS for health care reform. The U.S. health system could not have accomplished this feat without case managers and social workers. Implications for Case Management: Acute care services should be very proud of their achievements and use their reputation to empower their work for the next frontier, which will be reducing cost per case, especially in risk contracts. Everything old seems new again.